2023
DOI: 10.3390/diagnostics13122075
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Elastography to Assess Age of Deep Vein Thrombosis: A Systematic Review

Abstract: Background and aims: Deep-vein thrombosis (DVT) is a widely diffused condition, and its accurate staging has major clinical and therapeutic implications. Ultrasound elastography (UE) is a rapidly evolving imaging technique that allows quantification of elastic tissue properties and could play a crucial role in determining thrombus age. The aim of this review is to find clinical evidence regarding the application of UE in the evaluation of DVT and its usefulness in differentiating thrombosis age. Methods: A lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…No interobserver variability was assessed for CDVT diagnosis and clot measurement, and some concern may exist regarding the homogeneity of the diagnostic procedure in the study. [25] Notably, all ultrasound tests were performed by board-certified vascular medicine physicians using a standardized examination protocol, and previous studies [26] have shown that compression ultrasound yields satisfactory inter-agreement. Finally, the non-rehabilitation group of patients with MCVT was small, and larger studies are required in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…No interobserver variability was assessed for CDVT diagnosis and clot measurement, and some concern may exist regarding the homogeneity of the diagnostic procedure in the study. [25] Notably, all ultrasound tests were performed by board-certified vascular medicine physicians using a standardized examination protocol, and previous studies [26] have shown that compression ultrasound yields satisfactory inter-agreement. Finally, the non-rehabilitation group of patients with MCVT was small, and larger studies are required in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, various other imaging modalities such as 99mTc-recombinant tissue plasminogen activator scintigraphy imaging, 18 F-fluorodeoxyglucose positron emission tomography–computed tomography ( 18 F-FDG PET/CT), and US elastography have been developed for detecting acute thrombosis or to differentiate acute thrombosis from chronic thrombosis. 31 32 33 However, these radiological techniques have only been studied to a limited extent and have not found their way into clinical practice.…”
Section: Evolution In Imaging Techniques To Diagnose Deep Vein Thromb...mentioning
confidence: 99%
“…An in vivo rabbit model study 27 could successfully separate acute from chronic thrombi with shear wave (SW) elastography. Such results have been less conclusive in humans 29–32 ; readers may consult a systematic review of clinical studies for details 33 . The clot's resistance to thrombolytics has also been related to its stiffness and mass density 23 .…”
mentioning
confidence: 99%